Various Insights Highlighting the Significance of Empirical Studies in Customary Legal Research (Beberapa Catatan tentang Pentingnya Penelitian Hukum Adat Empiris) - Pradhani, Sartika Intaning (The Indonesian Journal of Socio-Legal Studies, 2023)
Mainstream Customary (Adat) Law does not pay much attention to empirical legal research; therefore, it is adat-positive legal science. In fact, adat law lives in a continuously changing community; thus, isolating its study from social research has made adat legal science has lost the opportunity to find perpetual adat legal development. This paper explains the significance of social research for adat legal science. Empirical data have numerous functions, such as legal materials to draft Academic papers on laws and regulations related to the Adat Law Community, judges’ consideration in settling disputes, especially agrarian conflict, and supporting the Adat Law Community to formulate their rules for the sake of their community and environmental sustainability.